Особливості поновлення процесуальних строків у справах, в яких сторонами виступають шукачі захисту - Калашник, Олена; Kalashnyk, О. (ТНЕУ, 2019)
Проаналізовано права біженців або осіб, які потребують додаткового захисту в контексті права на поновлення процесуальних строків. Обґрунтовано пропозиції щодо вдосконалення забезпечення права шукачів захисту та членів їх родин на поновлення процесуальних строків. Автором проаналізовано судову практику щодо поновлення процесуальних строків у справах за позовами шукачів захисту в Україні до Державної міграційної служби України про визнання протиправним та скасування рішень про відмову у визнанні їх біженцями або особами, які потребують додаткового захисту. Наведено основні проблеми дотримання прав шукачів захисту на поновлення процесуальних строків. In this article analyzes the rights of refugees or persons who need of additional protection regarding the sustainability of family ties and family reunification in cases of recognition of asylum seekers and their family members by refugees or persons who need of additional protection by the State Migration Service of Ukraine and courts. Suggestions are made to improve the protection of rights of asylum seekers and their family members to reunite families and ensure the sustainability of family ties. The author also provides recent research on the legal status of refugees or persons who need of additional protection. The list and analysis of the main international and national normative legal acts in the sphere of securing the rights of asylum seekers and their family members for family reunification and ensuring the sustainability of family ties are presented. The judicial practice on cases of claims of asylum seekers in Ukraine to the State Migration Service of Ukraine for recognition as illegal and the cancellation of decisions refusing to recognize them as refugees or persons who need of additional protection are analyzed. The main problems are the observance of the rights of asylum seekers regarding the sustainability of family ties and the reunification of their families in Ukraine. In the article analyzes that the European Court of Human Rights has taken the position of prioritizing the sustainability of family ties and family reunification in cases of recognition of the asylum seeker and his or her family as refugees. The author gives an example of the decision of the European Court of Human Rights on the topic of this article. The author concludes that in order to solve the problems of ensuring the priority of the sustainability of family ties and reunification of the family in cases of recognition of the asylum seeker and his family as refugees, courts of Ukraine should apply the positive practice of the European Court of Human Rights. The article describes cases of restrictions on ensuring the sustainability of family ties and restrictions on the right of reunification of family of asylum seekers in Ukraine.
Peculiarities of the Renewal of Procedural Terms in Cases in Which Parties are Asylum Seekers
Keywords: права біженців; процесуальний строк; шукач захисту; позов про визнання протиправним та скасування рішення; Європейський суд з прав людини; the rights of refugees; procedural time limit; asylum seeker; lawsuit for recognition as illegal and annulment of the decision; European Court of Human Rights